LEMIERRE SYNDROME: A FORGOTTEN INFECTION - Ullah, Raza; Shahada Naz; Haleema (Journal of Ayub Medical College Abbottabad, 2024)
Lemierre’s syndrome is a serious disease caused by an anaerobic bacteria called Fusobacterium necrophorum, which usually occurs in healthy teenagers and adolescents. The infection takes place in the throat and spreads through septic thrombosis of the tonsillar and internal jugular veins. The resulting bacterial infection is complicated by septic emboli in several places such as the lungs, joints and bones. Fever, pharyngitis, dysphagia, odynophagia, or swelling of the oropharyngeal is a common symptom. Although rare, there has been evidence of a recurrence of the condition in recent years, which may be associated with a reduction in the use of antibiotic therapy for the cold throat. The typical clinical image is characteristic, but many doctors do not recognize the condition and diagnoses are often delayed with potentially fatal consequences. We are presenting a similar case of Lemierre’s syndrome in an elderly female with pharyngitis, resulting in thrombophlebitis, empyema and discharging neck sinus.